2012
DOI: 10.2485/jhtb.21.451
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of the Antitumour Effect of Cisplatin by Administering Local Electrical Pulses to Metastatic Lesions of Hamster Oral Fibrosarcoma

Abstract: Electrochemotherapy (ECT) is currently receiving much attention as a method that can enhance the delivery of antitumour drugs into tumour cells by electroporation. In this study, we examined the effect of cisplatin on metastatic lesions of hamster oral fibrosarcoma by administering it in association with low-voltage electrical pulses. Oral fibrosarcoma was transplanted submucosally into the cheek pouches of 80 hamsters. After transplantation, when the diameter of the metastatic lesion in the left submandibular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Kodre et al (2009) reported that a variety of tumors of different histological origin such as fibrosarcomas, perianal tumours, sarcoids, mammary carcinoma and melanoma were treated with ECT with either cisplatin or bleomycin. Sugita et al(2012) demonstrated the anti-tumour effect of low-voltage electroporation on metastatic fibrosarcomas. Th e minimal voltage required for electroporation was > 900 V/cm.…”
Section: Resultsmentioning
confidence: 99%
“…Kodre et al (2009) reported that a variety of tumors of different histological origin such as fibrosarcomas, perianal tumours, sarcoids, mammary carcinoma and melanoma were treated with ECT with either cisplatin or bleomycin. Sugita et al(2012) demonstrated the anti-tumour effect of low-voltage electroporation on metastatic fibrosarcomas. Th e minimal voltage required for electroporation was > 900 V/cm.…”
Section: Resultsmentioning
confidence: 99%